Determinants of carbon dioxide emissions in technology revolution 6.0: new insights from Brunei - Vu Ngoc Xuan (Energy Strategy Reviews)
The manuscript explores the dynamic nexus between electricity consumption, renewable energy (REC), foreign direct investment (FDI), gross domestic product (GDP), and carbon dioxide (CO2) emissions within the context of Technology Revolution 6.0 in Brunei. The objective is to assess these variables' long- and short-term relationships, examining how economic growth and energy use affect environmental sustainability. A Vector Error Correction Model (VECM) approach is employed to capture the complex interrelationships and address the variables' integration order, followed by CUSUM and CUSUM of squares tests for model stability. The findings reveal that electricity consumption, GDP, and FDI significantly and positively impact CO2 emissions, while REC significantly and negatively impacts CO2 emissions. The results indicate a significant positive long-run impact of EC, GDP on CO2 emissions, with a 1 % increase in EC, GDP associated with the 0.45 % and 0.59 % rise in emissions, suggesting Brunei's reliance on fossil fuel-driven economic growth. Conversely, renewable energy shows a negative correlation with CO2 emissions, as a 1 % increase in renewable energy use leads to a 0.32 % reduction in emissions. FDI was found to increase emissions, with a 1 % rise in FDI contributing to a 0.27 % increase in CO2 emissions, indicating a pollution haven effect. These findings underscore the importance of economic diversification, stricter FDI regulations, and accelerated renewable energy adoption in reducing Brunei's environmental impact. Policy recommendations emphasize aligning Brunei's Vision 2035 with global sustainability goals, enhancing CO2 rules, and promoting low-carbon economic sectors.